Effects of core stability exercises on balance ability of children and adolescents with intellectual disabilities: A systematic review and meta-analysis - Zhou, Junjie; Zhong, Yecheng; Xu, Wenhong (PloS one, 2024)
Children and adolescents with intellectual disabilities (IDs) are at risk of falls due to balance problems. One way to palliate balance deficits among this population is via core stability exercises. However, comprehensive studies that examine the effectiveness of core stability exercises in improving balance in this target population are lacking. This study aims to summarise and quantify the effectiveness of core stability exercises in improving the balance of this target population. This study followed PRISMA principles and conducted comprehensive searches in six academic databases (PubMed, Web of Science, Medline, Embase, Scopus, and the Cochrane Library) up to June 2023. The inclusion criteria were established via the PICOS framework. The risk of bias was assessed with the Cochrane risk-of-bias tool, and the certainty of the evidence was assessed via the GRADE approach. The meta-analysis was performed via RevMan 5.4, and for data that could not be pooled via meta-analysis, we used a narrative description of the results of each study. Six studies of 1078 subjects were included. The findings revealed that core stability exercises improved the dynamic balance of children and adolescents with ID but had no significant effect on static (Hedges' g = 1.32, 95% CI [-0.41 to 3.06]) or static‒dynamic (Hedges' g = 1.35, 95% CI [-0.02 to 2.73]) balance compared with the control groups. The quality of evidence based on the GRADE approach was very low. Core stability exercises may improve dynamic balance in children and adolescents with ID, but given the scarcity of studies included, definitive conclusions cannot yet be drawn. Although pooled analyses also highlighted improvements in static and static-dynamic balance with large effect sizes over active control groups, the results were not statistically significant and should be interpreted with caution given the wide confidence intervals. The heterogeneity among the identified studies and the limited number of eligible studies may reduce the reliability of the results, but these findings emphasise the need for additional research in this domain.